Market Competition or Family Ties: Which Prevails on Italian CEOs Pay? - Clara Graziano; Laura Rondi (Center for Economic Studies and ifo Institute (CESifo), 2015)
The paper analyzes the interplay of product market competition and governance on CEO compensation in Italian listed firms from 2000 to 2011 and tests the impact of the 2007-08 financial crisis on pay-performance sensitivity. We argue that important differences both in the level of compensation and in its sensitivity to firm performance depend on two conditioning factors: family ownership and source of the competitive pressure. A novel aspect of our paper is that we rely on two definitions of competition: the intensity of import penetration, which accounts for price competition, and the intensity of R&D and advertising expenditures, which captures the oligopolistic nature of competition when products are vertically differentiated. Overall, the compensation of Italian CEOs is positively related to firm performance. Moreover, consistent with our predictions, sensitivity is higher in competitive sectors and the difference between family and non-family CEOs disappear when competition is tough. Family CEOs are significantly less paid than non-family CEOs and their pay is significantly related to firm performance. However, behind this sensitivity we find asymmetric responses to performance changes: while non-family CEOs pay mainly responds to negative changes, family CEOs pay is sensitive only to positive changes. Finally, we find that the 2007 financial crisis reduces the difference between family and non-family CEO by decreasing the level of compensation of non-family CEOs and increasing its responsiveness to performance. Altogether, our results provide supporting evidence to the idea that market competition eventually prevails over family ties even in a family-controlled governance system such as in Italy.
Keywords: G32; G34; 330; CEO compensation; product market competition; family firms; corporate governance; pay-performance sensitivity; financial crisis of 2007-2008